2009
DOI: 10.1021/bi901501a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Rate-Determining Step of tRNA-Guanine Transglycosylase from Escherichia coli

Abstract: The modified RNA base queuine (7-(4,5-cis-dihydroxy-1-cyclopenten-3-ylaminomethyl)-7-deazaguanine) occurs in tRNA via a unique base exchange process catalyzed by tRNA-guanine transglycosylase (TGT). Previous studies have suggested the intermediacy of a covalent TGT-RNA complex. To exist on the reaction pathway, this covalent complex must be both chemically and kinetically competent. Chemical competence has been demonstrated by the crystal structure studies of Xie et al. (Nature Structural Biology (2003) 10, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…However the K M values are much closer (within an order of magnitude), with the exception of the quadruple mutant, which is 100-fold higher than wild-type. Previously, we have shown that some mutants of C145 exhibit increased k cat and K M values [15], consistent with our determination that product release is rate-limiting [20], i.e., poorer binding due to a faster off-rate would result in faster k cat and larger K M . Additional mutations of the other residues cause decreases in k cat and increases in K M to relatively smaller extents (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…However the K M values are much closer (within an order of magnitude), with the exception of the quadruple mutant, which is 100-fold higher than wild-type. Previously, we have shown that some mutants of C145 exhibit increased k cat and K M values [15], consistent with our determination that product release is rate-limiting [20], i.e., poorer binding due to a faster off-rate would result in faster k cat and larger K M . Additional mutations of the other residues cause decreases in k cat and increases in K M to relatively smaller extents (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Derived from fit to the following equation: To determine which subunit (hQTRT1 or hQTRTD1) is actually responsible for the transglycosylase activity, two human TGT mutants, ht-hQTRT1(D279N) d hQTRTD1 and ht-hQTRT1 d hQTRTD1(E272Q), were expressed and purified. The corresponding residue, aspartate 264, in the E. coli TGT is the nucleophilic catalyst that forms the covalent RNA-TGT intermediate (Kittendorf et al 2003;Xie et al 2003;Garcia et al 2009). Mutation to anything other than glutamate yields catalytically inactive protein that is structurally unaltered (i.e., it folds correctly and binds, noncovalently to tRNA).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the captured covalent intermediate is converted to the product by soaking preQ 1 into the crystals, demonstrating its intermediacy in the catalytic cycle [73]. Site-directed and kinetic studies have confirmed the role of the Asp and have demonstrated kinetic competence for the covalent intermediate [74,75]. …”
Section: Enzymes Involved In the Biosynthesis Of Deazapurinesmentioning
confidence: 99%